Pengaruh Risiko Bisnis, Ukuran Perusahaan Dan Likuiditas Terhadap Harga Saham Dengan Struktur Modal Sebagai Variabel Intervening - Unsong, Imelda F (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
This study aims to examine the effect of business risk, firm size and liquidity on stock prices with the capital structure as an intervening variable (case study on textile companies listed on the Indonesia Stock Exchange in 2013 - 2017). The analysis technique uses path analysis (path analysis) with the AMOS program to assist in analyzing.The results of the study show that business risk has a significant influence on capital structure. Company size does not have a significant effect on capital structure. Liquidity has a significant influence on capital structure. Business risk does not have a significant effect on stock prices. Company size does not have a significant effect on stock prices. Liquidity does not have a significant effect on stock prices. Capital structure does not have a significant effect on stock pricesKeywords: Business Risk, Company Size, Liquidity, Capital Structure, Stock Prices